2010
DOI: 10.1021/pr900898n
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Tumor Necrosis Factor-α-Induced Secretome of Human Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Human adipose tissue-derived mesenchymal stem cells (hASCs) are useful for regeneration of inflamed or injured tissues. To identify secreted hASC proteins during inflammation, hASCs were exposed to tumor necrosis factor-alpha (TNF-alpha) and conditioned media derived from hASCs were analyzed by liquid chromatography coupled with tandem mass spectrometry. We identified 187 individual proteins as secreted proteins (secretome) in hASC-conditioned media; 118 proteins were secreted at higher levels upon TNF-alpha t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
168
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(175 citation statements)
references
References 54 publications
6
168
0
1
Order By: Relevance
“…2C). A recent study reported that SH3BGRL3 is upregulated in the secretome of human adipose tissue-derived mesenchymal stem cells upon TNFa treatment (18). SH3BGRL3 was classified as a nonclassical secretory protein ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C). A recent study reported that SH3BGRL3 is upregulated in the secretome of human adipose tissue-derived mesenchymal stem cells upon TNFa treatment (18). SH3BGRL3 was classified as a nonclassical secretory protein ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we corroborate that marked upregulation of PTX3 gene expression and protein content by IL-1␤ and TNF␣ in cultured SGBS adipocytes is parallel to increased protein secretion. Indeed, secretion of PTX3 protein from different stimulated cell types has been demonstrated, e.g., in rodent 3T3-F442A adipocytes (1), AT-derived mesenchymal stem cells (25), monocytes, endothelial cells and fibroblasts (3,20), myoblasts (20), FS4 fibroblasts, and Hep3B hepatocytes (23). In conclusion, our data in cultured adipocytes suggest that some proinflammatory factors elevated in AT in obesity such as IL-1␤ (22) and TNF␣ (19) may contribute to the upregulation of PTX3 production in the VAT depots of obese subjects, whereas other obesityrelated factors such as AT oxidative stress and hypoxia or hyperinsulinemia do not substantially regulate PTX3 gene expression in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PTX3 has different cell-specific gene expression and ligand-binding properties from CRP (8). PTX3 is produced in response to proinflammatory signals by mononuclear phagocytes (3,20), myeloid dendritic cells (12), fibroblasts (9,20,23), endothelial cells (9,20), hepatic cells (9), myoblasts (20), synoviocytes (26), lung epithelial cells (17), renal epithelial cells (32), adipocytes (1), AT-derived mesenchymal stem cells (25), and smooth muscle cells (11). Expression of the PTX3 gene increases in human cultured myotubes compared with the skeletal muscle tissue (38).…”
mentioning
confidence: 99%
“…cell type: ASC, 31 fibroblasts, 32 and keratinocytes 21 10 ng/mL TNF-a (R&D Systems); granulocytes 10 nM N-Formylmethionyl-leucyl-phenylalanine (fMLP) (GenScript, Piscataway, NJ) 33 ; monocytes 100 ng/mL Lipopolysaccharides (LPS) (Sigma-Aldrich) 34 ; or HMVEC 10 ng/mL vascular endothelial growth factor (VEGF) (PrepoTech, Rocky Hill, NJ). 18 Culture supernatants were harvested (granulocytes after 4 h, monocytes after 16 h, and ASC, fibroblasts, keratinocytes, and HMVEC after 24 h) and stored at -20°C for further analysis by ELISA.…”
Section: Differential Response Of Skin Cells To Wound Bed Environmentmentioning
confidence: 99%